Clinical and pharmacological characteristics of elderly patients admitted for bleeding: impact on in-hospital mortality. (2nd October 2020) - Pani, Arianna; Pastori, Daniele; Senatore, Michele; Romandini, Alessandra; Colombo, Giulia; Agnelli, Francesca; Scaglione, Francesco; Colombo, Fabrizio
Abstract: Introduction: Clinical and pharmacological characteristics of elderly patients hospitalized for bleeding and in-hospital mortality according to bleeding type are barely described. Methods: Retrospective cohort study of 13, 496 consecutive patients admitted to internal medicine wards. Clinical characteristics, comorbidities and pharmacological treatments were collected for each patient. Predictors of in-hospital mortality were investigated. Results: Overall, 531 (3.9%) patients were admitted for bleeding: 189 clinically relevant non-major bleeding, 106 cerebral and 236 major non-cerebral (95.8% gastrointestinal (GI)). Among 106 cerebral bleedings, 28.3% and 24.5% were typical and atypical intracranial, respectively, and 47.2% were subdural haemorrhages. Most of patients with GI bleeding presented with anaemia (90.7%). A similar rate of GI bleeding was found in aspirin-treated patients taking or not proton pump inhibitors (PPI). In-hospital mortality was 9.98%. Age ≥80 years (odds ratio (OR) 2.513, p =.005), cerebral bleeding (OR 5.373, p <.001), eGFR <30 ml/min/m 2 (OR 2.388, p =.035) and COPD (OR 2.362, p =.024) were positively associated with mortality, while ACE inhibitors/ARBs use was negatively associated (OR 0.383, p =.028). Conclusions: The most frequent type of major haemorrhage was GI bleeding, which was not modified by the use of PPI in patients taking aspirin. Cerebral bleeding increased all-cause death, which was lower in ACE inhibitors/ARBs users. KEY MESSAGE: Gastrointestinal (GI) bleeding was the most common reason for hospital admission. The rate of GI bleeding was similar in patients on aspirin using or not PPI. Cerebral bleeding increased in-hospital mortality, which was lower in patients taking ACE inhibitors/ARBs.